Success of Business Management Education in the Family: Systematic Literature Review (SLR) - Sriarianie Sriarianie; Hanik Munaddifah; Tita Ratnawati; Ludi Wishnu Wardana; Aniek Indrawati; Bagus Setiawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
There are various kinds of business applications in this country, including one of them is a business in the family. Business management education in the family is very important to ensure the survival of each family member. This research is a systematic literature review (SLR) that discusses the success of business education and management in the family. Literature study research is a process or activity of collecting data from various literatures such as books and journals to compare the results of one research with another. There are 10 articles related to the success of business management education in the family, these 8 journals will be used in answering the next problem formulation. From several articles that have been reviewed, there are several determining factors for the success of business management education in the family including Market Assessment, Understanding Customer Satisfaction, Understanding Innovation Development, and Being Able to Find Appropriate Human Resources.